Severe multivessel coronary heart disease in a young woman with familial hypercholesterolemia and congenital heart disease: A case report - Shaikh B. Iqbal; Shraddha Poudel; Nicholas Huerta; Ajay Kumar; Sean Shieh; Shiavax J. Rao (Elsevier, 2024)
The prevalence of premature atherosclerotic cardiovascular disease (ASCVD) ranges from 7% to 30%, but the incidence in young patients is increasing. Traditional risk factors, such as hypertension, hyperlipidemia, obesity, and diabetes, have an increasing prevalence in young patients and especially in young women. A 32-year-old woman presented with dyspnea and exertional chest pain. She had a history of familial hypercholesterolemia and unidentified aortic valve disease status after a pulmonary autograft at the age of 20. Due to insurance changes with the onset of the COVID-19 pandemic, she lost access to specialty care. She was not on any cholesterol-lowering agents prior to admission. An electrocardiogram demonstrated no ST changes with elevated high-sensitivity troponin-I concerning for non-ST elevation myocardial infarction. Laboratory data also revealed elevated LDL-C greater than 400. Due to concern for multivessel disease and complex anatomy, she underwent coronary computerized tomography angiography, which verified her multivessel coronary artery disease. An echocardiogram demonstrated a preserved ejection fraction and moderate aortic regurgitation. Her coronary artery bypass graft was deferred due to possible future valvular surgery. She underwent percutaneous coronary intervention with drug-eluting stents to left circumflex and left anterior descending arteries. Familial hypercholesterolemia is a prevalent but under-recognized and under-treated risk factor for premature ASCVD, which can be adequately identified through improved risk assessment and managed with aggressive combination anti-hyperlipidemia therapy.